CLIMATE DURING THE PERMIAN-TRIASSIC BIOSPHERE REORGANIZATIONS. ARTICLE 2. CLIMATE OF THE LATE PERMIAN AND EARLY TRIASSIC: GENERAL INFERENCES - Chumakov N.M.; Zharkov M.A. (My University, 2003)
The Late Permian-initial Triassic was a period of the Earth climate change, as the glacial climate of the Late Paleozoic was replaced by the non-glacial one of the Mesozoic. The intricate trend of this process is reconstructed and illustrated by schematic paleoclimatic maps. Warming in the second half of the Sakmarian Age resulted in a rapid degradation of huge glacial belt to the polar glacial cap. By the Kazanian Age, the latter was gradually replaced by the high-latitude temperate-cold belt with retained and new glacial centers that inter- mittently widened. In the Tatarian Age, a similar temperate-cold belt appeared in the Northern Hemisphere as well. The next strong and sudden global warming occurred in the Permian-Triassic boundary period when the temperate-warm climate developed in high latitudes of the Northern Hemisphere and temperate one in the Southern Hemisphere. General warming complicated by frequent different-rank oscillations transformed the climatic zoning on the Earth and resulted in rapid global ecological changes. Huge dimensions of Pangea and mountainous belts and ridges at its margins primordially determined wide development of the semiarid and arid climate in low latitudes. During the Late Permian-initial Triassic period, the aridity of the Earth was increasing that is evident from successive widening of arid and semiarid belts of Pangea, which advanced toward middle latitudes, and from grown aridity in the equatorial mountainous belt and in tropical latitudes of the Tethys. Glo- bal warming was main factor responsible for stepwise widening of arid and semiarid belts. Another cause of aridity increase was gradual regression of inner seas. Arid and semiarid belts occupied about 40% of land at the beginning of the Early Permian, 55% in the late Sakmarian-early Artinskian time, and 80% in the Induan Age. Paleoclimatic reconstructions confirm the assumed significance of monsoons impact on the climate develop- ment in the Permian and Early Triassic to a certain extent only. During glacial periods, the climatic asymmetry of the Earth was particularly remarkable. Registered environmental changes of the Permian time (regressions, aridity growth, land elevation, orogeny, and island-arc volcanism) could result only in cooling. Warming of terminal Permian-Early Triassic, as well as C, O, S, and Sr isotopic anomalies were probably the first results of the main Pfalzian phase of the Hercynian tectogenesis with associated weakening of suprasubduction volcanism, intense regional metamorphism, and denudation of carbonaceous sedimentary sequences of orogens. The subsequent outburst of mantle volcanism, in particular, trap eruptions in Siberia promoted these processes further. Depending on their scale, climatic changes prepared or even provoked biotic crises, the mass extinctions included.
Keywords: Triassic; Permian; Mesozoic::Triassic; Мезозой::Триасовая; Paleozoic::Permian; Палеозой::Пермская